PEDAGOGICAL FOUNDATIONS OF INTERDISCIPLINARY INTEGRATION AND FORMS OF CURRICULAR SUBJECT INTEGRATION - Begmatova Dilfuza Abdullajanovna; Ergasheva Mahfuza Salievna (Web of Journals Publishing, 2025)
The complex demands of modern education have elevated interdisciplinary integration as a pivotal strategy within the learning process, facilitating the formation of a holistic knowledge system and the development of students’ cognitive and practical competencies. This study aims to deeply explore the pedagogical foundations of interdisciplinary integration and analyze the various forms of curricular subject integration. The article systematically examines the interconnections between disciplines such as physics, mathematics, biology, chemistry, and information technologies, evaluating their impact on educational outcomes. The findings affirm the effectiveness of interdisciplinary approaches in enhancing critical thinking, problem-solving abilities, and the application of contextual knowledge, while identifying thematic, problem-based, and project-based integration as the most effective models. This work contributes to global discussions on pedagogical innovation and offers evidence-based approaches for curriculum design.
Keywords: Interdisciplinary integration, pedagogical foundations, curricular subjects, educational outcomes, thematic integration, problem-based learning, project-based learning, cognitive competencies, contextual learning, didactic innovations.